Saúde do professor: uso de medicamentos por professores da rede estadual de educação de Rio Verde/Goiás - Ferreira , Thayrene Vieira (2016)
The teaching profession is considered by the International Labor Organization (ILO) as one of the most stressful. Research indicates that there is precariousness in the organization, conditions and professional relationships and link this precarization to the illness that affects these professionals. In view of this, this study sought to analyze the use of medications by teachers of the state education network of Rio Verde / GO and associate it with determining factors. This is a cross-sectional descriptive and analytical study with a qualitative-quantitative approach, which had 289 teachers. The data were analyzed with the support of the software SPSS® 23.0, in order to verify if any variables were associated with the use of medicines, the Chi-square test or the Student t-test was performed. The prevalence of medication use among teachers in the 15-day recall period was 79.2%. 155 active ingredients were used in a total of 538 pharmaceutical specialties. The mean use was 1.86 medication per person (SD 1.87). Of the teachers surveyed, 88.9% of them reported self-medication. The most commonly used drug was dipyrone (8.55%). The most used drugs were nervous system (29.6%), musculoskeletal system (19.5%) and digestive system and metabolism (17.3%). The female gender was associated with the use of drugs, the perception that the medicine poses a risk to health, self-medication, chronic diseases, not interruption of activities due to health problems, medical consultations in the last three months; no other paid activity, excessive workload and consider that work affects health. The precariousness of teachers' work was revealed in this research by the devaluation of the class, by bad remuneration, by the intensification of teaching activity, by violence in schools and by strenuous journeys. Teachers inserted in this context and in the logic of medication, use medicines as a way to alleviate the suffering that the teaching practice has brought to their health. There are many challenges to be overcome in reaching teachers' health, and they involve intervening in the various stressors related to teaching work, and involve better salaries, valorization, social recognition, improvement in the school infrastructure, support of parents, students, School management, and thus in fact, do not allow medicines to occupy the undue place of health symbols, but that really teachers have decent working conditions and quality of life.